Hypnotherapy Intervention for the Treatment of Insomnia in A 26 Years-Old Woman with General Anxiety Disorder: A Case Report - Hutomo, Yudhistira (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Hypnotherapy is a method that engages a person in relaxation and leads them into a trance-like condition. There are many benefits that can be obtained by doing hypnotherapy, one of which is to overcome sleep disorders or insomnia. Insomnia refers to a disruption or irregularity in sleep manifested as ongoing challenges in falling asleep or staying asleep and/or waking up too early. Anxiety is often linked to difficulties with sleep. Increased anxiety and fear can hinder the ability to both initially fall asleep and remain asleep throughout the night. In this case report, we report a female patient who complained of insomnia for 2 years. Patients complain that it is very difficult to start sleeping. In addition, patients also experience various symptoms such as fatigue, lack of focus and muscle tension in the neck and several places. This patient underwent hypnotherapy and found that the root of the problem was an anxiety disorder that she had not been aware of. This anxiety disorder is also confirmed by anamnesis and symptoms experienced by the patient and assessment using the Hamilton Rating Scale for Anxiety (HAM-A). After the hypnotherapy session, we followed up with the patient for one week after the therapy session. Patients show significant changes with better sleep quality and reduced patient anxiety symptoms.